PENGGUNAAN TEPUNG JAHE (Zingiber officinale var. Amarum) PADA PAKAN IKAN PATIN (Pangasius Sp) UNTUK MENGOBATI INFEKSI Aeromonas hydrophila - Mohamad Amin; Tanbiyaskur Tanbiyaskur; Jimmy Rifanji (Jurnal Akuakultur Rawa Indonesia, 2022)
Ginger is one type of traditional plant that can be used to control Motile Aeromonas Septicemia (MAS) disease which attacks catfish (Pangasius sp) cultivation. This study aims to determine the effect of ginger powder added to feed to treat A. hydrophila infection in catfish. The research was conducted at the Aquaculture Laboratory, Study Program of Aquaculture, Faculty of Agriculture, Sriwijaya University in October 2020. This study used a completely randomized design (CRD) consisting of 6 treatments (T) with 3 replications, namely (T0) without the addition of ginger flour, ( T1) adding 10 g.kg-1  ginger flour, (T2) adding ginger flour 12.5 g.kg-1, (T3) adding ginger flour 15 g.kg-1, (T4) adding ginger flour 17.5 g.kg-1  and (T5) adding ginger flour 20 g.kg-1. The parameters observed were length and weight growth, total erythrocytes, total leukocytes, larvae survival, water physics and chemistry (temperature, pH, DO and ammonia). The results of this study indicate that the best treatment is found at (T5) with an absolute weight growth of 6.25 grams, an absolute length growth of 1.09 cm, 90.00% survival. During maintenance the water quality is at conditions 27-29 0C for temperature, water pH 6-7, dissolved oxygen 5.00 mg.L-1, and ammonia 0.005-0.040 mg.L-1.Key words : Aeromonas hydrophila, Catfish, Ginger, Essential oil